Approach and Avoidance Behavior in Female Patients With Borderline Personality Disorder - Wiesenfeller, Jana; Flasbeck, Vera; Brown, Elliot C.; Brüne, Martin (Frontiers in Behavioral Neuroscience, 2020)
Objectives Borderline personality disorder (BPD) is portrayed by unstable relationships, fears of abandonment and heightened sensitivity to social rejection. Research has shown that these characteristics may lead to inappropriate social behavior including altered approach-avoidance behavior. However, it has remained unclear how social exclusion may affect approach-avoidance behavior in patients with BPD. Design We assessed social approach-avoidance behavior and the impact of social exclusion in a sample of 38 patients with BPD and 40 healthy control participants. Methods We used an explicit joystick-based approach-avoidance task (AAT) after playing a virtual ball-tossing game (Cyberball), which simulates the exclusion of the participant by two other players. In the AAT, participants were required to push or pull emotional stimuli, more specifically happy and angry facial expressions, with either direct or averted gaze direction. Results Patients with BPD approached happy stimuli less and showed overall less differential approach-avoidance behavior toward individuals expressing positive or negative facial emotions compared to healthy participants, who showed more approach behavior for happy compared to angry facial expressions. Moreover, borderline symptom severity correlated inversely with the AAT score for happy facial expressions and positively with subjective unpleasantness during social exclusion as well as rejection sensitivity. However, social exclusion did not influence approach-avoidance tendencies. Conclusion Patients with BPD showed altered approach-avoidance behavior, which might affect social interactions in the patient’s everyday lives and may therefore impede social interaction.